Management activities of a tutor in modern Chinese universities - Lyu Qiang; Люй Цянь (Kharkiv : V. N. Karazin Kharkiv national university, 2025)
Tutors’ managerial activities in modern Chinese universities are a vital component of the higher education talent cultivation system, combining academic guidance and student management. The study demonstrates that through policy implementation, model innovation, technology application, and collaborative cooperation, universities have accumulated substantial practical experience that effectively promotes students’ comprehensive development. Nevertheless, challenges remain, including uneven management quality, insufficient professional capabilities of tutors, and imperfect collaborative mechanisms. Optimization strategies include student-classification-based management, enhancement of tutors’ professional development, digital and intelligent management, and improved collaborative management mechanisms with clearly defined roles. Enhancing tutors’ managerial activities supports their role as “comprehensive educators,” enables integration of student management with moral education, provides high-quality talent support for China’s social and economic development, and offers valuable practical experience for the reform and improvement of the tutor system in Chinese universities.

Керівницька діяльність кураторів у сучасних китайських університетах є важливою складовою системи підготовки талантів у вищій освіті, поєднуючи академічне наставництво та управління студентами. Дослідження показало, що через політичне впровадження, інноваційні моделі, технологічне забезпечення та колабораційну взаємодію університети накопичили значний практичний досвід, що сприяє всебічному розвитку студентів. Водночас практична діяльність стикається з проблемами, такими як нерівномірна якість управління, недостатня професійна компетентність кураторів і неповноцінні механізми співпраці. Запропоновано шляхи оптимізації: диференційоване управління студентами, розвиток професійної майстерності кураторів, впровадження цифрового та інтелектуального управління, удосконалення колаборативних механізмів із чітким розподілом ролей. Покращення керівницької діяльності кураторів сприяє реалізації їхньої ролі як «всебічних педагогів», інтеграції управління студентами та морального виховання, забезпечує високоякісну підтримку талантів для соціального та економічного розвитку Китаю, а також формує практичний досвід для реформування системи кураторів у китайських університетах.
Управлінська діяльність викладача в сучасних китайських університетах
Supervisor: Nataliia Tkachova, doctor of pedagogical sciences, professor, professor of the Department of innovative pedagogy, educational transformations, and leadership
Keywords: SOCIAL SCIENCES::Social sciences::Education; tutors; tutors’ managerial activities; tutoring system in higher education; digital technologies in higher education; tutors’ professional development; цифрові технології у вищій освіті; тьютори; управлінська діяльність тьюторів; система наставництва у вищій освіті; професійний розвиток тьюторів